Event Priority Driven Dissemination EPDD Management Algorithm For Low Power WSN Nodes Powered By A Dual Source Energy Harvester - Abdal-Kadhim, Ali Mohammed; Kok, Swee Leong (Elsevier, 2020)
This paper proposes a low-power wireless sensor node which is able to deal with energy harvesting mismatches. The hardware incorporates thermoelectric and piezoelectric transducers for a dual energy harvester, energy storage, microcontroller, sensor and wireless transceiver. The software incorporates an energy-aware Event-Priority-Driven-Dissemination algorithm to send data based on priority or event occurrence. This algorithm serves both to detect the availability of the energy source and to control the nodes’ sleep mode. The outcomes revealed that the hardware power was 0.16 mW and 2.13 mW in sleep and active modes respectively. Also, energy autonomy was comfortably achieved since the dual harvester energy was 90 mW when both sources were available